The NADPH oxidase complexes in Botrytis cinerea: evidence for a close association with the ER and the tetraspanin Pls1. - Ulrike Siegmund; Jens Heller; Jan A L van Kan; Paul Tudzynski (PLoS ONE, 2013)
NADPH oxidases (Nox) are major enzymatic systems that generate reactive-oxygen species (ROS) in multicellular eukaryotes. In several fungi they have been shown to be involved in sexual differentiation and pathogenicity. However, in contrast to the well characterized mammalian systems, basic information on the composition, recruitment, and localization of fungal Nox complexes and on the molecular mechanisms of their cellular effects are still lacking. Here we give a detailed analysis of components of the Nox complexes in the gray mold fungus Botrytis cinerea. It had previously been shown that the two catalytic transmembrane subunits BcNoxA and B are important for development of sclerotia and for full virulence, with BcNoxA being involved in spreading of lesions and BcNoxB in penetration; BcNoxR functions as a regulator of both subunits. Here we present evidence (using for the first time a functional GFP fusion able to complement the ΔbcnoxA mutant) that BcNoxA localizes mainly to the ER and at the plasma membrane; BcNoxB shows a similar localization pattern, while the regulator BcNoxR is found in vesicles throughout the hyphae and at the hyphal tip. To identify possible interaction partners, which could be involved in the localization or recruitment of the Nox complexes, we functionally characterized the tetraspanin Pls1, a transmembrane protein, which had been suggested to be a NoxB-interacting partner in the saprophyte Podospora anserina. Knock-out experiments and GFP fusions substantiate a link between BcNoxB and BcPls1 because both deletion mutants have overlapping phenotypes (especially a defect in penetration), and the proteins show a similar localization pattern (ER). However, in contrast to the corresponding protein in P. anserina BcPls1 is important for female fertility, but not for ascospore germination.